Enhancing 5G network performance through effective resource management with network slicing - Suganthi, Nagarajan; Narasimhan Ganesh, Enthrakandi; Guruva Reddy, Elangovan; Balakumar, Vijayaraman; Ilakkiya, Thangam; Varadarajan, Mageshkumar Naarayanasamy; Ramesh Babu, Venkatachalam (Institute of Advanced Engineering and Science, 2024)
The immense growth of mobile networks leads to versatile applications and new demands. The improved concert, transferability, flexibility, and performance of innovative network services are applied in diversified fields. More unique networking concepts are incorporated into state-of-the-art mobile technologies to expand these dynamic features further. This paper presents a novel system architecture of slicing and pairing networks with intra-layer and inter-layer functionalities in 5th generation (5G) mobile networks. The radio access network layer slices and the core network layer slices are paired up using the network slicing pairing functionalities. The physical network elements of such network slices will be logically assigned entities called softwarization of the network. Such a novel system architecture called network sliced softwarization of 5G mobile networks (NSS-5G) has shown better performances in terms of end-to-end delay, total throughput, and resource utilization when compared to traditional mobile networks. Thus, effective resource management is achieved using NSS-5G. This study will pave the way for future softwarization of heterogeneous mobile applications.